Dispersion stability and density of palm oil based suspension of Al2O3-TiO2hybrid nanofluid - Najib N.A.; Wanatasanappan V.V. (American Institute of Physics Inc., 2024)
The study of nanofluid stability is vital to fully utilize its potentials, particularly to improve nanofluid qualities. This experimental work focuses on the preparation and evaluation of the dispersion stability palm oil based suspension of Al2O3-TiO2 hybrid nanofluid. Five different mixing ratio mixture of 20:80, 40:60, 50:50, 60:40 and 80:20 of Al2O3-TiO2 nanoparticles were dispersed in palm oil using two step method. The volume concentration of the hybrid nanofluid was set as a constant variable throughout this experimental study at 0.5%. Sodium Dodecyl Sulfate (SDS) were used as surfactant to stabilize the nanoparticle mixture in the base fluid. The stability of Al2O3-TiO2 hybrid nanofluid was visually observed after the preparation and constantly observed from time to time for an interval period. UV-Vis spectrometer and density measurement were conducted in this experimental study to observe the effect of nanoparticle ratio on the stability of Al2O3-TiO2 hybrid nanofluid with palm oil suspension. Lastly, this experimental study findings and results for stability of Al2O3-TiO2 hybrid nanofluid will helps in developing a new experimental study that will be effective with stability of hybrid nanofluid and mixture ratio of nanoparticles in future studies. 2023 Author(s).